The Contribution of Selected Instructional Methods Toward Graduate Student Understanding of Crisis Communication - Christy Witt; David Doerfert; Tracy Rutherford; Theresa Murphrey; Leslie Edgar (Journal of Applied Communications, 2011)
Providing quality instruction that meets students’ learning needs is an issue facing teachers of agriculture in higher education. A considerable amount of research has been devoted to assessing the effectiveness of various instructional methods, but the research is inconclusive in identifying a singular method of instruction that works well with all individuals. The purpose of this study was to examine students’ perceived value of instructional methods in contribution towards their understanding of and confidence in risk and crisis communication content and practices. This study also compared students (N = 30) from two semesters to determine if new instructional methods incorporating new technology (i.e., Second Life) impacted the knowledge, comprehension, and self-confidence of students. In this descriptive survey research, the data revealed that students did not identify one singular instructional method as being most beneficial and influential, but found a combination of instructional methods influenced their self-confidence. No significant differences were found in changes in students’ content knowledge scores or end-of-course degree of confidence scores.
Keywords: Second Life; crisis communication; instructional methods; effectiveness